# Binomial Expansions

The sum $a+b$ is called a binomial as it contains two terms.
Any expression of the form $(a+b)^n$ is called a power of a binomial.

Binomial Expansions

All binomials raised to a power can be expanded using the same general principles. In this lesson, therefore, we consider the expansion of the general expression $(a+b)^n$ where $n \in \mathbb{N}$.

Consider the following algebraic expressions.
\begin{align} \displaystyle (a+b)^1 &= a^1 + b^1 \\ &= a+b \\ (a+b)^2 &= a^2 + 2a^1b^1 + b^2 \\ &= a^2 + 2ab + b^2 \\ (a+b)^3 &= a^3 + 3a^2b^1 + 3a^1b^2 + b^3 \\ &= a^3 + 3a^2b + 3ab^2 + b^3 \\ \end{align}

From the theory of Pascal's Triangle, the coefficients of binomial expansions are coming from Pascal's Triangle. \begin{matrix} n=0&&&&&&1 \\ n=1&&&&&1&&1 \\ n=2&&&&1&&2&&1 \\ n=3&&&1&&3&&3&&1 \\ n=4&&1&&4&&6&&4&&1 \\ \end{matrix}
Let's consider the expansion of $(a+b)^4$. This expansion produces $5$ terms; $a^4;a^3b^1;a^2b^2;a^1b^3;b^4$.
Their corresponding coefficients are $1;4;6;4;1$ respectively as per Pascal's Triangle.
Therefore we can obtain the expansion of $(a+b)^4$ by combining these terms and coefficients. \begin{align} \displaystyle (a+b)^4 &= 1a^4 + 4a^3b^1 + 6a^2b^2 + 4a^1b^3 + 1b^4 \\ &= a^4 + 4a^3b + 6a^2b^2 + 4ab^3 + b^4 \\ \end{align}

### Example 1

Expand $(a+b)^5$.

### Example 2

Expand $(a-b)^5$.

### Example 3

Expand $(a+2b)^5$.

### Example 4

Expand $\bigg(a+\dfrac{1}{a}\bigg)^3$.